Decision-making and Effectiveness of Business Results in Times of COVID-19 - Carlos Arturo Hoyos-Vallejo (International Review of Management and Marketing, 2021)
Managers often make decisions in organizations without being aware of the results and hence, their effectiveness. I evaluated three decisions managers made during the first weeks of the COVID-19 pandemic, using a hypothetical model of the decision-making process (DMP) so as to measure the percentage of effectiveness business results (PEBR) achieved. This article analyzes the impact of DMP on PEBR and identifies similarities and differences among top performing managers. Results reveal that the model not only predicts the PEBR, but also there are positive associations between the predictor variables that give meaning to validates the model, so I designed a comparative scenario by gender, age, company size, highlighting the profile of the managers with the best results. To understand the relationship between DMP and PEBR academics must adopt a perspective that considers not only the acceptance of decisions, but also distinguishes the association forces DMP variables; and managers can use this decision-making model to improve the process and the expected results. Practical implications, limitations and future studies are discussed.